Creating, nurturing and building conducive environment for lifelong learning in Malaysia: The Ulū Al-Albāb approach - Mhd. Sarif, Suhaimi; Benjasom, Muhammad Husnee (2013)
This paper postulates the Ulū al-Albāb approach in creating, nurturing, and building conducive environment for lifelong learning in Malaysia. The Ulū al-Albāb approach is spiritual-based knowledge management that offers an integrative framework to achieve sustainable knowledge management and organizational learning. The existing lifelong learning approach lacks of spirituality foundation to sustain the motivation for continuous learning and development among knowledge workers. An opinion survey with knowledge workers who are familiar with conventional lifelong learning perceived that the Ulū al-Albāb approach is commendable insights into dynamism, uncertainty and complex business contexts. The current stage of the Ulū al-Albāb approach has to be operationalized to fit into the contemporary business models and processes. However, the views of the knowledge workers are not comprehensive and rigorous without the views from other stakeholders. Nevertheless, managers can apply the Ulū al-Albāb approach into its communities of practice and social network. The Ulū al-Albāb approach contributes to the theoretical and practical understanding of knowledge management development.